Assessment of three electrolyte–molecule electrostatic interaction models for 2D material based BioFETs. Issue 3 (14th December 2018) - Toral-Lopez, A.; Marin, E. G.; Gonzalez-Medina, J. M.; Romero, F. J.; Ruiz, F. G.; Morales, D. P.; Rodriguez, N.; Godoy, A.
Abstract : A comprehensive simulation of 2D materials based BioFETs that simultaneously assesses different approaches employed to model the electrolyte-molecule interaction. Abstract : BioFETs based on two-dimensional materials (2DMs) offer a unique opportunity to enhance, at a low cost, the sensitivity of current biosensors enabling the design of compact devices compatible with standard CMOS technology. The unique combination of large exposed surface areas and minimal thicknesses of 2DMs is an outstanding feature for these devices, and the assessment of their behaviour requires combined experimental and theoretical efforts. In this work we present a 2D-material based BioFET simulator including complex electrolyte reactions and analysing different models for the electrolyte–molecule interaction. These models describe how the molecular charge is screened by the electrolyte ions when their distributions are modified. The electrolyte simulation is validated against experimental results as well as against the analytical predictions of the Debye–Hückel approximation. The role of the electrolyte charge screening as well as the impact of the interaction model on the device responsivity are analysed in detail. The results are discussed in order to conclude about the consequences of employing different interaction approximations for the simulation of BioFETs and more generally on the correct modelling of biomolecule-device interaction in BioFETs.